ipod and itunes for dummies ebook - Bove, Tony (Dummies., 2011)
The perennial iPod and iTunes bestseller and ideal companion is completely updated! Now in its ninth edition, iPod & iTunes For Dummies is the ultimate beginner's guide for getting started with the iPod and Apple's iTunes service. Bestselling veteran author Tony Bove helps you get comfortable with using the iPod as more than just a digital music player. You'll learn to record videos and take pictures, video chat with FaceTime, surf the web, rent movies, buy songs, send and receive e-mail, get directions, and much more. Completely revised throughout, this fun and friendly book walks you through using iTunes to import music, videos, apps, books, and podcasts as well as burn CDs, sync with iPod, and play music through your home stereo. Offers straightforward coverage of using your iPod as the ultimate digital music player and shows you how to choose the iPod model that's right for you, get started with your iPod, set up iTunes, master the touch interface, and shop at the iTunes store Teaches you how to add music tracks from a CD to your iTunes library, play content in iTunes, set up playlists, share content from your iTunes library, and manage photos and videos Escorts you through the processes for sending and receiving e-mail, downloading and using apps, fine-tuning sound, updating and troubleshooting, and maintaining battery life Tune in! iPod and iTunes For Dummies, 9th Edition, guides you through all the latest updates and enhancements so that you can start enjoying iTunes and your iPod today!